Modelling the diffusion of the deterrent effects of competition policy - Adriaan H. Dierx; Fabienne Ilzkovitz; Beatrice Pataracchia; Filippo Pericoli (European Commission, 2022)
Through its competition policy interventions the European Commission not only addresses infringements of EU competition law by the firms directly involved, but it also deters possible future anticompetitive behaviour by these firms and other market players. The present paper represents the diffusion amongst market players of such deterrent effects by a mixed-influence diffusion model, which includes both an external triggering factor and an internal propagation mechanism. Within the present context, interventions by the European Commission serve as the trigger and interactions between market players, in particular via legal counsels and law firms, stimulate the propagation of the interventions' deterrent effects. The parameters of the mixed-influence diffusion model are calibrated using surveybased information on average deterrence multipliers and an assessment of the reputation of the European Commission as an enforcer of EU competition rules. On this basis, estimates of the deterrent effect of each individual intervention by the European Commission can be obtained. A sensitivity analysis shows that small interventions by a competition authority having a good reputation have larger deterrent effects than the same interventions by competition authorities with a worse reputation. However, this difference is less pronounced for interventions affecting large markets. Similarly, an increase in interactions between legal counsels and law firms has important positive effects on deterrence, in particular for smaller interventions. Finally, the sensitivity of the deterrent effects to changes in interactions is rather similar to the sensitivity to changes in reputation, with the exception for cartel enforcement, where the interactions between legal counsels and law firms have a much greater impact.
Keywords: 330; diffusion; deterrent effect; competition policy; European Commission; mixed-influence model; reputation